2016
DOI: 10.1155/2016/2196986
|View full text |Cite
|
Sign up to set email alerts
|

Association between IgG4 Autoantibody and Complement Abnormalities in Systemic Lupus Erythematosus

Abstract: In order to investigate the association between IgG4 autoantibody and complement abnormalities in systemic lupus erythematosus (SLE), 72 newly diagnosed SLE patients, 67 rheumatoid arthritis (RA) patients, and 41 healthy normals were employed. Serum levels of antinuclear IgG4 and IgG4-specific IgM-rheumatoid factor (RF) were measured, and the correlations between serum levels of antinuclear IgG4 and several clinical parameters were analyzed. Also, the levels of IgG subclasses, C1q, and C3 deposition in lupus n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…It is speculated that ANA IgG1 and IgG4 have high affinity in the cutaneous and renal types in the serum cycle and play an important role in the disease process in SLE. Certain studies have reported that the serum levels of IgG4 were significantly higher in SLE patients who were also more likely to exhibit interstitial pneumonia and pancreatic involvement, 20,21 in accordance with our results of the IgG4 subclass of pulmonary involvement in SLE patients. In vivo , immunoglobulin IgG4 is generally regarded as an immunoglobulin that does not activate immune effector cells and induces complement formation, thus mediating the anti-inflammatory response.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is speculated that ANA IgG1 and IgG4 have high affinity in the cutaneous and renal types in the serum cycle and play an important role in the disease process in SLE. Certain studies have reported that the serum levels of IgG4 were significantly higher in SLE patients who were also more likely to exhibit interstitial pneumonia and pancreatic involvement, 20,21 in accordance with our results of the IgG4 subclass of pulmonary involvement in SLE patients. In vivo , immunoglobulin IgG4 is generally regarded as an immunoglobulin that does not activate immune effector cells and induces complement formation, thus mediating the anti-inflammatory response.…”
Section: Discussionsupporting
confidence: 92%
“…9 Moreover, we found that the level of ANA IgG4 in LN patients was significantly higher than that in non-LN patients and was positively related to the serum levels of albumin and HA IgG ANA, which was in accordance with Pan’s report. 20 Although no relationship was noted between ANA IgG4 and the C3/C4 complement, it is suggested that the IgG4 autoantibody could compete with IgG1, IgG2, or IgG3 for connecting autoantigens, which resulted in fewer ICs. 23 ICs containing IgG4-autoantigen have a low affinity for Fc receptors and C1 complement molecules, and thus, their ability to induce an immune response is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most subclasses of IgG, including IgG2, IgG3, and IgG4, were highly expressed in the skin tissues of patients with SLE [ 28 ]. Moreover, the levels of IgG4, but not those of IgG3, were higher in the serum of patients with SLE than in those of patients with RA or HCs, and the ratio of IgG4/IgG1-4 was negatively correlated with a complement deposition [ 29 ]. In addition, a study investigating the B-cell receptor repertoire in immune-mediated diseases, including SLE, showed that the levels of the IgA1/2 and IgG1/2 isotypes, but not those of the IgG3 isotype, were significantly higher in patients with SLE compared to the HCs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human serum C3 and C4 were detected by rate nephelometry using a Beckman IMMAGE 800 analyzer (Beckman-Coulter, Carlsbad, USA). Serum creatinine, blood urea nitrogen (BUN), 24-h proteinuria, urine protein, and creatinine levels were measured with a Cobas 8000 automatic biochemistry analyser (Roche Diagnostics, GmbH, Mannheim, Germany), and 24h urinary protein was measured with an Olympus AU2700 automatic biochemistry analyzer (Olympus Corporation, Tokyo, Japan) (32). Human serum complement factor B and factor H were quantified using commercially available ELISA kits (Abcam, Inc., Cambridge, MA, USA).…”
Section: Serum and Urine Assaysmentioning
confidence: 99%